Leviathan transformed : seven national states in the new century - Caplow, Theodore (Comparative charting of social change., 2001)
Leviathan Transformed is based on the premise that a national state is a particular type of organization and, at any given time and like any other organization, its performance can be evaluated with reasonable objectivity. The authors, an international team of eminent social scientists, examine the performance of seven states: Bulgaria, Canada, France, Italy, Germany, Spain, and the United States. These nations pursue similar goals - union, justice, tranquillity, defence, welfare, liberty - which, in one form or another, are common to all democracies.